Longitudinal Tumor Size and Neutrophil‐to‐Lymphocyte Ratio Are Prognostic Biomarkers for Overall Survival in Patients With Advanced Non‐Small Cell Lung Cancer Treated With Durvalumab. (21st December 2020) - Gavrilov, Sergey; Zhudenkov, Kirill; Helmlinger, Gabriel; Dunyak, James; Peskov, Kirill; Aksenov, Sergey
Abstract : Therapy optimization remains an important challenge in the treatment of advanced non‐small cell lung cancer (NSCLC). We investigated tumor size (sum of the longest diameters (SLD) of target lesions) and neutrophil‐to‐lymphocyte ratio (NLR) as longitudinal biomarkers for survival prediction. Data sets from 335 patients with NSCLC from study NCT02087423 and 202 patients with NSCLC from study NCT01693562 of durvalumab were used for model qualification and validation, respectively. Nonlinear Bayesian joint models were designed to assess the impact of longitudinal measurements of SLD and NLR on patient subgrouping (by Response Evaluation Criteria in Solid Tumors 1.1 criteria at 3 months after therapy start), long‐term survival, and precision of survival predictions. Various validation scenarios were investigated. We determined a more distinct patient subgrouping and a substantial increase in the precision of survival estimates after the incorporation of longitudinal measurements. The highest performance was achieved using a multivariate SLD and NLR model, which enabled predictions of NSCLC clinical outcomes.